2006
DOI: 10.1093/annonc/mdj084
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab and irinotecan/5-fluorouracil/folinic acid is a safe combination for the first-line treatment of patients with epidermal growth factor receptor expressing metastatic colorectal carcinoma

Abstract: Addition of cetuximab to weekly infusional 5-FU/FA plus irinotecan is safe and first data suggest a promising activity. The 5-FU dose of 1500 mg/m(2) is recommended for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(106 citation statements)
references
References 18 publications
7
91
0
8
Order By: Relevance
“…Emerging data suggest that the addition of targeted biological agents to such regimens will further improve efficacy. Indeed, Folprecht et al (2006) reported a median survival time of 33 months, using cetuximab, an EGFRtargeted monoclonal antibody, in combination with irinotecan/5-FU/FA. In a randomised phase III trial, cetuximab was shown to increase response rate, progression-free survival and resection rate over FOLFIRI alone in patients with advanced CRC, with the PFS benefit being greatest for those patients with liver-only metastases (Van Cutsem et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data suggest that the addition of targeted biological agents to such regimens will further improve efficacy. Indeed, Folprecht et al (2006) reported a median survival time of 33 months, using cetuximab, an EGFRtargeted monoclonal antibody, in combination with irinotecan/5-FU/FA. In a randomised phase III trial, cetuximab was shown to increase response rate, progression-free survival and resection rate over FOLFIRI alone in patients with advanced CRC, with the PFS benefit being greatest for those patients with liver-only metastases (Van Cutsem et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab was subsequently investigated first-line in combination with irinotecan/infusional 5-FU/FA (Rougier et al, 2004;Folprecht et al, 2006). Initial results showed these combinations to be safe with promising activity.…”
Section: Cetuximabmentioning
confidence: 99%
“…Cetuximab has a mean volume of distribution of 45.2-61.9 ml/kg, approximately equivalent to plasma volume, at intravenous doses of 20-100 mg/m 2 given at weekly intervals for 4-12 weeks, as demonstrated in two phase I studies (Folprecht et al, 2005). The major route of cetuximab clearance is through binding of the antibody to EGFR in many tissues, including the liver and the skin, which subsequently internalizes the antibody-receptor complex and removes it from circulation (Baselga et al, 2000;Robert et al, 2001;Folprecht et al, 2005). Cetuximab clearance decreases with increasing dose, indicating saturation of the metabolic pathway and nonlinear pharmacokinetics at lower doses.…”
Section: Molecular Properties and Clinical Pharmacologymentioning
confidence: 97%
“…In patients with metastatic CRC treated with cetuximab 400 mg/m 2 as initial dose followed by 250 mg/m 2 weekly in association with irinotecan either alone or with FA and 5-FU, mean peak serum concentrations of 153-202 mg/ml and the area under the plasma concentration-time curve values of 21 520-17 337 mg/h/ml were recorded between weeks 1 and 4 of treatment (Debaldo et al, 2003;Folprecht et al, 2005). Cetuximab has a mean volume of distribution of 45.2-61.9 ml/kg, approximately equivalent to plasma volume, at intravenous doses of 20-100 mg/m 2 given at weekly intervals for 4-12 weeks, as demonstrated in two phase I studies (Folprecht et al, 2005).…”
Section: Molecular Properties and Clinical Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation